(untitled) (Advancements in Homeopathic Research, 2023)
Introduction: Microbial content in homeopathic mother tincture (MT) is a critical quality parameter. It is an essential procedure of in-process quality control (IPQC). However, it requires time and resources. It is a known fact that a high concentration of alcohol does not allow microbial growth. Many mother tinctures are with high alcohol content. But the threshold level of alcohol content from which it inhibits microbial growth is not yet known. This study is an attempt to create a distinct demarcation for grouping the mother tinctures as high risk and low risk for microbial growth potential based on the alcohol content (AC). This will help to apply skip testing to optimize the resources.Materials & Method: Microbial data of mother tinctures for 5 years was taken retrospectively for the analysis and they were grouped into high alcohol content (HAC, containing more than 50% alcohol) and low alcohol content (LAC, containing less than 50% alcohol). Mother tinctures with microbial count below 10,000 were considered as low risk (LR) and above 10,000 were considered high risk (HR). The correlation of HAC and LAC with LR & HR was analyzed in different ratios and the threshold level of low risk with respect to alcohol content was identified.Results: There were 2804 batches taken for the data analysis of which 76.78% batches were of HAC and 23.22% batches were of LAC. Within HAC, 99.95% of MTs fell under LR. Whereas in LAC, 89.86% fell under HR. Conclusion: Homeopathic mother tinctures containing alcohol content more than 50% have low risk in terms of microbial content. Further, some mother tinctures, which contain alcohol content less than 50%, fall under low risk category. Categorizing mother tinctures based on the risk for microbial content will help to optimise quality control resources and to apply the skip testing method.